Pengembangan Konten Canva Sebagai Media Pembelajaran Untuk Meningkatkan Motivasi Belajar Siswa: Development of Canva Content as Learning Media to Increase Student Motivation - Asrori, Muhammad Abdul Roziq; Koiriyah, Koiriyah; Purwananti, Yepi Sedya (Universitas Nusantara PGRI Kediri, 2023)
This research aims to develop Canva Application Content as an information technology-based learning media to increase student motivation at SMAN 1 P. This Research and Development has succeeded in developing Canva application content as an information technology-based learning medium using a model from Thiagarajan known as the 4-D model; Define, Design, Develop and Disseminate. Researchers used quantitative descriptive data analysis techniques that showed the assessment of the validator was 83.33% with a very decent category. The effectiveness of learning media by developing Canva application content in increasing the learning motivation through a limited-scale trial, there was an increase of 70% of students who achieved the passing grade, while based on the results of the Paired Sample T-Test there was a significant difference between the pretest and posttest with a score of the significance is 0.001 while in the wider respondent trial, the results of Improved Learning Outcomes are 40% of students who achieve the passing grade before (Pretest) and 93% after (Posttest), while based on the results Paired Sample T-Test test there is a significant difference between pretest and posttest with a significance value of 0.000. This identifies that the learning media is effective in increasing students' learning motivation.